Atypical phenotype of a patient with Bardet–Biedl syndrome type 4. Issue 5 (23rd March 2022) - Sloboda, Natacha; Lambert, Laetitia; Ciorna, Viorica; Bruel, Ange‐Line; Tran Mau‐Them, Frédéric; Gomola, Vladimir; Lemelle, Jean‐Louis; Klein, Olivier; Camoin‐Schweitzer, Marie‐Christine; Magnavacca, Marie; Legagneur, Carole; Ezsto, Marie‐Laure; et al.
Abstract: Background: Bardet–Biedl syndrome (BBS) is a multisystemic disorder characterized by rod–cone dystrophy, truncal obesity, postaxial polydactyly, cognitive impairment, male hypogonadotropic hypogonadism, complex female genitourinary malformations, and renal abnormalities. There is a large clinical and also genetic heterogeneity in BBS. Here, we report a patient with polydactyly, hyperechogenic kidneys increased in size with normal corticomedullary differentiation, anal imperforation, and malformation of genitals with presence of a genital tubercle with ventral urethral meatus associated with two unfused lateral genital swelling and absent urethral folds, in the context of 46, XY karyotype. Methods: Karyotype and solo exome sequencing were performed to look for a genetic etiology for the features described in our patient. Results: We identified a homozygous in‐frame deletion of exons 4 to 6 in the BBS4 gene (NM‐033028 (BBS4‐i001): c.[(157‐?)_(405 +?)del] p.(Ala53‐Trp135del), which is classified as pathogenic variant. This analysis allowed the molecular diagnosis of BBS type 4 in this patient. Conclusion: Complex genital malformations are only reported in female BBS6 patients yet, and genital abnormalities and anal imperforation are not reported in male BBS4 patients to date. We discuss the possible hypotheses for this phenotype, including the phenotypic overlap between ciliopathies. Abstract : Here, we report a patient with polydactyly, renal particularities, anal imperforation, and malformation of genitals in the context of 46, XY karyotype. Complex genital malformation and anal imperforation are not reported in male BBS4 patient to date. We discuss the possible hypotheses for this phenotype, including the phenotypic overlap between ciliopathies.